Collider bias undermines our understanding of COVID-19 disease risk and severity - Gareth J. Griffith (Nature Portfolio, 2020)
Many published studies of the current SARS-CoV-2 pandemic have analysed data from non-representative samples from populations. Here, using UK BioBank samples, Gibran Hemani and colleagues discuss the potential for such studies to suffer from collider bias, and provide suggestions for optimising study design to account for this.